Transposon-Mediated Horizontal Transfer of the Host-Specific Virulence Protein ToxA between Three Fungal Wheat Pathogens - McDonald, Megan C. (mBio, 2019)
Most known examples of horizontal gene transfer (HGT) between eukaryotes are ancient. These events are identified primarily using phylogenetic methods on coding regions alone. Only rarely are there examples of HGT where noncoding DNA is also reported. The gene encoding the wheat virulence protein ToxA and the surrounding 14 kb is one of these rare examples. ToxA has been horizontally transferred between three fungal wheat pathogens (Parastagonospora nodorum, Pyrenophora tritici-repentis, and Bipolaris sorokiniana) as part of a conserved ∼14 kb element which contains coding and noncoding regions. Here we used long-read sequencing to define the extent of HGT between these three fungal species. Construction of near-chromosomal-level assemblies enabled identification of terminal inverted repeats on either end of the 14 kb region, typical of a type II DNA transposon. This is the first description of ToxA with complete transposon features, which we call ToxhAT. In all three species, ToxhAT resides in a large (140-to-250 kb) transposon-rich genomic island which is absent in isolates that do not carry the gene (annotated here as toxa(−)). We demonstrate that the horizontal transfer of ToxhAT between P. tritici-repentis and P. nodorum occurred as part of a large (∼80 kb) HGT which is now undergoing extensive decay. In B. sorokiniana, in contrast, ToxhAT and its resident genomic island are mobile within the genome. Together, these data provide insight into the noncoding regions that facilitate HGT between eukaryotes and into the genomic processes which mask the extent of HGT between these species.